Perancangan Sistem Informasi Kepegawaian Menggunakan Metode Fast Pada Badan Usaha Bandar Udara Hang Nadim Batam: Personnel Information System Design Using the Fast Method at Batam Hang Nadim Airport Business Entities - Albertus Laurensius Setyabudhi; Doni Syofiawan; Enggar Adi Sulityo (YCMM, 2021)
The Hang Nadim Airport Business Entity in managing employee data is currently still carried out separately or not properly structured where the data created by the personnel manager is not integrated and has not been managed unified in one application or program. The aim of the researcher is to build a staffing system at BUBU that can be managed and structured to monitor all personnel data in the form of a web-based system dashboard. The implementation of this web-based system will use FAST (Framework for the Application of System Thinking) as a system development, life cycle because after the implementation and maintenance stages are completed, the system will provide feedback to the designed analysis, so that these stages are continuously carried out to improve the system. . The reason the author chooses the FAST method is because this method has completeness and is more detailed in the research and system development process. The system built makes it easy for employees to be more independent in processing data, and for the HR and General department admins have access to updating periodic salary increases (KGB) and regular promotions based on online.